ASSYLUM-SEEKER CHILDREN’S MIGRATION FROM EAST TO WEST: THE MEANING OF CARE FOR UNACCOMPANIED MINORS - Ulugbekov O.O. (TARIXIY TADQIQOTLAR, 2025)
Today, the number of unaccompanied asylum-seeker children is increasing in the global world due to various reasons. They escape from the risky life in their country and come to the developed, peaceful countries of the world to save their lives. The UK is also one of their destinations. In this essay, we will explore why unaccompanied children come to the UK and what difficulties they face here. Specifically, what kind of approach to unaccompanied children in foster care is the crucial element for their happiness, and whether their living period in foster care is enough to heal from the mental and physical trauma they experienced and specific issues in transition to adulthood. Based on these issues, we will consider what care means for unaccompanied children and how the meaning of care transfers as they grow older. We use Honnoth's theory of recognition to find answers to the questions.